2011
DOI: 10.1016/j.leukres.2011.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the use of NG2 antigen as a marker to predict MLL rearrangements in multi-center studies

Abstract: Rearrangements in MLL (MLL-r) are common within very young children with leukemia and affect the prognosis and treatment. Previous studies have suggested the use of the NG2 molecule as a marker for MLL-r but these studies were performed using a small number of infants. We analyzed 148 patients (all less than 24 months, 86 less than 12 months) from various centers in Brazil to determine the predictive power of NG2 within that cohort. We show that NG2 can be used for MLL-r prediction; however, proper staff train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…KRAS mutations have also been associated with higher WBC counts and poor disease evolution (36) and have been found subclonally present at birth in matched neonatal blood spot diagnosis samples (14). Furthermore, in a MA4 þ transgenic mouse model, activated KRAS accelerated leukemogenesis, although the phenotype did not reproduce that seen in patients (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KRAS mutations have also been associated with higher WBC counts and poor disease evolution (36) and have been found subclonally present at birth in matched neonatal blood spot diagnosis samples (14). Furthermore, in a MA4 þ transgenic mouse model, activated KRAS accelerated leukemogenesis, although the phenotype did not reproduce that seen in patients (15).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the paucity of mutations observed in WGSeq studies, activating mutations in the RAS signaling pathway were found in half of the patients (9)(10)(11)(12), and previous screenings of infants with MA4 þ pro-B-ALL also found RAS mutations in approximately 25% of patients that correlated with poor outcome. KRAS mutations have also been associated with higher WBC counts (13) and found subclonally present at birth in neonatal blood spots (14). Furthermore, in a MA4 þ transgenic mouse model, activated KRAS accelerated leukemogenesis, although the latency/phenotype did not reproduce that seen in patients (15).…”
Section: Introductionmentioning
confidence: 99%
“…27 Although it might be associated with the high propensity of this leukemia to infiltrate the CNS, its exact contribution to disease evolution remains a mystery. [28][29][30] In infant B-ALL, MLL-r is associated with poorer outcome. In the Children's Cancer Group protocol CCG-1953, the 5-year event-free survival (EFS) for MLL-r infants was 34% compared with 60% with germline MLL.…”
Section: Clinical Features Of T(4;11)mentioning
confidence: 99%
“…KMT2A rearrangements are frequently accompanied by neuron‐glial antigen 2 (NG2) surface expression with the highest correlation accuracy in infant BCP‐ALL and lower accuracy in AML . Our patients showed NG2 expression in 13 of 28 cases (46%) with no preference to the particular KMT2A breakpoint localization.…”
Section: Discussionmentioning
confidence: 72%